The need to update Ethiopia’s national health and medicine policies: essential tools for informed decision-making in healthcare and the pharmaceutical sectors - Bayked, Ewunetie Mekashaw (Frontiers in Public Health, 2025)
BackgroundHealth policy involves decisions at national, state, and local levels to achieve healthcare goals, with medicine policy being a critical component that requires integration and potential reform. The World Health Organization (WHO) recommends periodic monitoring and evaluation of the National Medicine Policy (NMP) under the National Health Policy (NHP), ideally every 2 to 3 years or comprehensively every 4 to 5 years.ObjectivesThis perspective aims to urge the Ministry of Health (MOH) of Ethiopia to update its national health and medicine policies to address emerging health issues, advancements in medical treatment, and global health agendas. It also aims to initiate a name change for Ethiopia’s “NDP” to “NMP” to focus on medicines for therapeutic purposes while avoiding confusion with the term “drug.”MethodsA descriptive critical evidence synthesis was used to identify indicators and situations for monitoring, evaluating, and updating national health and medicine policies. The author presented published evidence to support the perspective that Ethiopia’s national health and medicine policies need to be updated.ResultsEthiopia’s national health and medicine policies have remained unchanged for over three decades, despite their critical role in guiding healthcare decision-making and reflecting political commitment to advancing healthcare goals through regular monitoring and evaluation. This underscores an urgent need to update these policies and periodically monitor and evaluate them at prescribed intervals: every 2 to 3 years for minor changes or every 4 to 5 years comprehensively. Additionally, the title “National Drug Policy (NDP)” should be changed to “NMP” to better reflect its focus on safe, effective, and approved medicines for healthcare, while avoiding negative associations with the general term “drugs”.ConclusionGiven the dynamic nature of the health and pharmaceutical sectors, it is crucial for Ethiopia to urgently update the NHP and NMP and change the NDP title to “NMP” to eliminate ambiguity, emphasize approved medicines, and align with global best practices.